Inductive source degenerative LNA for radar altimeters - Iyer, Makesh; Shanmuganantham, T (International Journal of Engineering and Technology, 2018)
This paper deals with the design of Low Noise Amplifier with inductive source degeneration technique using ADS simulation tool. The major parameters on which RADAR Altimeter working depends is the sensitivity and selectivity of the first RF amplifier after receiving antenna which captures all the available signals. But the rain attenuates the propagating EM waves which results in a distorted signal being received by the antenna. The LNA designed will improve the signal strength i.e. the gain and reduces the noise figure for better detection of earthâ€™s surface reflected radio signal at the receiver of aircraft. The low noise amplifier designed is with inductive source degeneration which is a stability improvement technique that proved to be an efficient and optimum design resulting in power gain of 14.735 dB and noise fig-ure of 0.132 dB.Â Â
Keywords: Altimeters; Inductive Source Degenerative LNA; Noise Figure; Power Gain; VSWR.